Analysis of children’s content on youtube channels by parents - Barcellos, Lívia Inglesis [UNESP]; Médola, Ana Sílvia Lopes Davi [UNESP]; Botura, Galdenoro [UNESP]; Barcellos, Ekaterina Emmanuil Inglesis [UNESP] (Springer Nature, 2020)
The advancement of technology and the evolution of the means of communication have enabled the proliferation and diversification of access to information, and the use of videos stood out among them. Through this media, thousands of people broadcast the entire range of content, from makeup tutorials to political debates. One of the best known websites for this is YOUTUBE, where, in recent years, there has been an increasing number of videos with children’s content and produced for, or by, children. This article presents an analysis of the channels of child youtubers and their content, based on a survey carried out with people responsible for children between 4 and 13 years old. In view of the results, it identifies the opinion of the parents regarding the quality of the content available, as well as the influence that the channels that stand out on the website have on the culture of youtubers.
Keywords: Child consumption; Parents; Youtube; Youtuber Mirim